Penatalaksanaan Teknik Radiografi Vertebrae Lumbosacral Pada Kasus Scoliosis di Rumah Sakit Islam Siti Khadijah Palembang - Anisah, Anisah; Pangesti, Putri; Tugiyanto, Tugiyanto (JURNAL KESEHATAN TERAPAN, 2024)
Scoliosis is a disorder that causes an abnormal curve of the spine. The purpose of this paper is to provide descriptive information about the management of the Lumbosacral Vertebrae radiographic technique in the case of Scoliosis, with the intention of knowing the radiographic techniques performed. The population in this study were all patients who examined Lumbosacral vertebrae who came to the Radiology Installation of the Islamic Hospital of Siti Khadijah Palembang, which was taken from one patient with Scoliosis in March. The radiographic technique for Lumbosacral examination is a projection of Posterior Antero (AP), the patient is in a supine position with both hands on the side of the body using the exposure factor Kv 80, mA 160 and Second 0, 250. In Lateral projection, the patient's position is directed in the Lateral position sideways on the examination table with the left side attached to the table using exposure factors kV 90, mA 200, and second 0.320. In patients with Scoliosis only use the AP position because it is at this position that the Cobb angle is visible. Radiographers provide correct direction to patients about the course of the examination so that it can produce an optimal picture.